2016
DOI: 10.1002/tee.22352
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal pseudo relevance feedback for scientific data retrieval

Abstract: We consider the problem of searching scientific data from vast heterogeneous scientific data repositories. This problem is challenging because scientific data contain relatively little text information compared to other search targets such as web pages. On the other hand, the metadata in scientific data contain other characteristic information such as spatio‐temporal information. Although using this information make it possible to improve the search performance, many widely adopted scientific data search engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…WordNet is typically the most common external tool used by global methods to select new candidate expansion terms that are semantically associated with the original query terms [7]. In contrast, local methods use relevance feedback, in which results from an initial retrieval are used to select the most promising terms to be added to the original query [8,9]. Pseudo Relevance Feedback (PRF), which assumes that the top-ranking k documents from the initial retrieval are relevant for selecting new terms, is a more favourable expansion technique as it automates manual relevance feedback.…”
Section: Introductionmentioning
confidence: 99%
“…WordNet is typically the most common external tool used by global methods to select new candidate expansion terms that are semantically associated with the original query terms [7]. In contrast, local methods use relevance feedback, in which results from an initial retrieval are used to select the most promising terms to be added to the original query [8,9]. Pseudo Relevance Feedback (PRF), which assumes that the top-ranking k documents from the initial retrieval are relevant for selecting new terms, is a more favourable expansion technique as it automates manual relevance feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have addressed similarities and differences between document and data search (Kern & Mathiak, 2015;Stempfhuber & Zapilko, 2009), emphasizing the need for new approaches and solutions with respect to the latter. As information objects, data are different from documents, for they are primarily numerical and non-textual (Takeuchi, Sugiura, Akahoshi, & Zettsu, 2017). Kern and Mathiak (2015) observed that users put much more effort in detailed querying of data, expressing locations, ranges and operators at an average word count of nine.…”
Section: Related Workmentioning
confidence: 99%
“…Another approach would be fostering the discovery of datasets according to their spatial and temporal properties. Despite their heterogeneity, inconsistency and incompleteness across different research communities and their corresponding repositories, around 73% of metadata records, e.g., from the PANGAEA repository hold information on spatial and/or temporal information as two basic characteristics of data (Takeuchi et al, 2017). According to DataCite's metadata schema 4.3, geolocation has become a mandatory metadata element with the properties for specifying both the longitude/latitude and the label of a geolocation.…”
Section: Discovering Datamentioning
confidence: 99%